A syntactic analysis of interpretive restrictions on imperative, promissive, and exhortative subjects - Zanuttini, Raffaella; Pak, Miok; Portner, Paul (Natural language and linguistic theory, 2012)
This paper investigates the interpretive restrictions on the subjects of imperative, promissive, and exhortative sentences—what we call the "jussive" clause types. It argues that the data cannot be explained by a theory that appeals only to semantic and pragmatic factors, and that an account crucially involving syntax is required. We propose that jussive clauses contain a functional head that bears a person feature. This head is an operator that, when in a sufficiently local configuration, binds the subject and enters an agreement relation with it. The restrictions in person features exhibited by the subjects are a consequence of this agreement relation. Moreover, we show that the syntactic structures produced by our analysis are compatible with a compositional semantics that yields the correct interpretation for imperatives and other jussives.